Exploration of the interactions between mitigation and solar radiation management in cooperative and non-cooperative international governance settings. (November 2018) - Emmerling, Johannes; Tavoni, Massimo
Highlights: Climate engineering, notably solar radiation management (SRM), is a controversial option. We evaluate the risk of climate engineering due to lack of international cooperation. Free driving leads to a significant overprovision of SRM. Countries in the tropics (India and others) have highest incentives for using SRM. Abstract: Growing concerns about climate change impacts on humans and eco-systems motivates exploring new strategies to complement traditional climate policies like mitigation and adaptation. Climate engineering via solar radiation management is one discussed option. However, climate engineering entails new risks, including its governance. Without sufficiently strong institutions, there is a risk that some countries will unilaterally deploy climate engineering to the detriment of other nations. This paper provides an evaluation of the risks of excess climate engineering due to lack of international cooperation. Using both an analytical and numerical model, we show how lack of cooperation leads to overprovision of climate engineering above what would be socially optimal. The regions with the highest climate change impacts deploy climate engineering at the expenses of the others. Yet, these poor countries still host the majority of the residual climate change impacts. These results suggest the importance of embedding climate engineering in the international climate policy debate.